Substitution of a residue contacting the triphosphate moiety of the incoming nucleotide increases the fidelity of yeast DNA polymerase ζ - Howell, Craig A. (Oxford University Press, 2008)
DNA polymerase ζ (pol ζ), which is required for DNA damage-induced mutagenesis, functions in the error-prone replication of a wide range of DNA lesions. During this process, pol ζ extends from nucleotides incorporated opposite template lesions by other polymerases. Unlike classical polymerases, pol ζ efficiently extends from primer-terminal base pairs containing mismatches or lesions, and it synthesizes DNA with moderate fidelity. Here we describe genetic and biochemical studies of three yeast pol ζ mutant proteins containing substitutions of highly conserved amino acid residues that contact the triphosphate moiety of the incoming nucleotide. The R1057A and K1086A proteins do not complement the rev3Δ mutation, and these proteins have significantly reduced polymerase activity relative to the wild-type protein. In contrast, the K1061A protein partially complements the rev3Δ mutation and has nearly normal polymerase activity. Interestingly, the K1061A protein has increased fidelity relative to wild-type pol ζ and is somewhat less efficient at extending from mismatched primer-terminal base pairs. These findings have important implications both for the evolutionary divergence of pol ζ from classical polymerases and for the mechanism by which this enzyme accommodates distortions in the DNA caused by mismatches and lesions.